HIV preexposure prophylaxis with tenofovir disoproxil fumarate/emtricitabine and changes in kidney function and tubular health. (1st April 2020) - Ascher, Simon B.; Scherzer, Rebecca; Estrella, Michelle M.; Shigenaga, Judy; Spaulding, Kimberly A.; Glidden, David V.; Mehrotra, Megha L.; Defechereux, Patricia; Gandhi, Monica; Grant, Robert M.; Shlipak, Michael G.; Jotwani, Vasantha
Abstract : Objective: To evaluate the effects of HIV preexposure prophylaxis (PrEP) with tenofovir disoproxial fumurate (TDF)/emtricitabine (FTC) on kidney function and kidney tubular health. Design: The Iniciativa Profilaxis Pre-Exposicion open-label extension (iPrEx-OLE) study enrolled former PrEP trial participants to receive open-label TDF/FTC. This study included 123 iPrEx-OLE participants who demonstrated PrEP adherence. Methods: We compared estimated glomerular filtration rate calculated using serum creatinine (eGFRcr), serum cystatin C (eGFRcys), and in combination (eGFRcr-cys), and a panel of 14 urine biomarkers reflecting kidney tubular health before and 6 months after PrEP initiation. Results: At baseline, mean eGFRcr, eGFRcys, and eGFRcr-cys were 108.3, 107.0, and 111.1 ml/min per 1.73 m 2, respectively. Six months after PrEP initiation, eGFRcr declined by −4% (95% CI: −5.7 to −2.4%), eGFRcys declined by −3.3% (95% CI: −8.3 to 1.9%), and eGFRcr-cys declined by −4.1% (95% CI: −7.5 to −0.7%). From the urine biomarker panel, α1-microglobulin and β2-microglobulin increased by 22.7% (95% CI: 11.8–34.7%) and 14.1% (95% CI: −6.1 to 38.6%), whereas chitinase-3-like 1 protein and monocyte chemoattractant protein-1 decreased by −37.7% (95% CI: −53.0 to −17.3%) and −15.6% (95% CI: −31.6 to 4.2%), respectively. Ten of the 14 urine biomarkers, including albumin, had estimated changes of less than 12% with wide confidence intervals. Conclusion: Six months of PrEP with TDF/FTC was associated with decreases in eGFRcr and eGFRcys. We also observed for the first time changes in flour of 14 urine biomarkers reflecting kidney tubular health. These findings demonstrate that PrEP has direct effects on eGFR and the proximal tubule. Abstract : Supplemental Digital Content is available in the text